El Samurái Fitness y su incidencia en el sobrepeso - Cargua Barsallo, Cristhian Fernando (2023)
The main objective of this research study entitled "Samurai Fitness" and its impact on overweight and obesity in children aged 5 to 9 years, had as its main objective to know the impact of the practice of samurai fitness, is an innovative training activity that combines fitness activities, displacements, and stretching with different techniques of combat sports with musical accompaniment and how it influences the body weight of the children of the Unidad Educativa "Guasuntos". This type of sporting activity can be adaptable to different stages of development, from infancy (5 to 11 years) to even older adults (60 years or more), as the intensity and complexity of the exercise can be increased or decreased according to our established purposes. This activity helps to burn calories and stimulates the body's metabolic processes. When performing this activity, it should be taken into account that it should be done at a rhythm that increases our heart rate, as this will be a favorable factor for the reduction of body fat. The present investigation used a qualitative-quantitative approach, with a cross-sectional, quasi-experimental design, the sample with which we worked was not selected randomly, but was selected before the results of the weight indicators, and was made up of 26 students from the Unidad Educativa "Guasuntos" who had excess of body weight. The research instruments used were the Body Mass Index test and the Height-Waist Index, once the formula had been carried out, it helped us to select the sample and the influence that the execution of the samurai fitness pre-post intervention had.